Synthesis and characterisation of core-shell structure PLA/CS/NIF nanoparticles. (24th May 2019) - Chinh, Nguyen Thuy; Duc, Le Ngoc; Trung, Trinh Hoang; Huynh, Mai Duc; Giang, Nguyen Vu; Cong, Do Van; Trang, Nguyen Thi Thu; Mai, Tran Thi; Thai, Nguyen Thi; Lam, Tran Dai; Hoang, Thai
To decrease the dissolution of chitosan (CS) in acidic environment, in this paper, poly(lactic acid) (PLA) and CS have been selected to prepare the PLA/CS core-shell structure nanoparticles loading the nifedipine drug (NIF), in which, CS containing NIF is core and PLA is shell. Coating PLA outside the CS carrying drug nanoparticles can help to protect the CS/drug particles in acidic environment of stomach so that the drug is not released or released slowly there. Then, the CS/drug nanoparticles is transported to the small intestine where is frequently perfused by blood, resulting in the most effective absorption of drug in the body. The properties of CS/NIF nanoparticles coated by PLA have been evaluated by Fourier transform infrared spectroscopy (FT-IR), laser scattering, dynamic light scattering (DLS) and differential scanning calorimetry (DSC) methods. The appearance of characteristic peaks for PLA, CS, and NIF in the FTIR spectra of nanoparticles shows that the CS/NIF nanoparticles are covered by PLA. The DLS diagrams indicate that the CS/NIF nanoparticles coated by PLA with a thickness of PLA film about 70-140 nm. The DSC diagrams of CS/NIF nanoparticles coated by PLA film show their melting temperature less than that of the CS/NIF nanoparticles. From the above results, it can be seen that the core-shell structure PLA/CS/NIF nanoparticles is prepared successfully. In addition, NIF release from the CS/NIF nanoparticles and core-shell structure PLA/CS/NIF nanoparticles are investigated and presented. The NIF release from the nanoparticles is a function of pH of immersed solution, immersed time and NIF content. The PLA coating helps to control the NIF release from the core-shell structure PLA/CS/NIF nanoparticles in acidic solution better than that from the CS/NIF nanoparticles at the same testing condition. The different kinetic models of drug release are also calculated and reported in order to perform the type of NIF release mechanism.